A Comparative Analysis of Manual and System-Based Recording of School Payments: Analisis Perbandingan Pencatatan Pembayaran Sekolah Secara Manual dan Berbasis Sistem - Aini Rachman, Iranda Qiro’atul; Noor Abidin , Fityan Izza (Indonesian Journal of Education Methods Development, 2023)
This qualitative study aims to compare the recording of payments manually and through a system at the school payment receivables level. The research took place in Sidoarjo and employed data obtained from interviews, observations, and documentation. The results showed that there are both advantages and disadvantages to each recording process, and the two systems cannot be equated. While manual recording provides a backup in case of system errors, the system facilitates monitoring of the total level of bad debt by the school treasurer. The study concludes that there is a significant difference in the recording of payments between the manual and system-based approaches. The findings have implications for school administrators and treasurers in deciding which recording method to use for efficient payment management. Highlight: Different recording methods: The study compares manual and system-based recording of school payments, highlighting the differences and trade-offs between the two approaches. Interrelatedness of manual and system recording: While each method has its advantages and disadvantages, they are interconnected, providing backup and ease of monitoring for school treasurers. Implications for payment management: The findings have implications for efficient payment management in schools, requiring considerations of reliability, efficiency, and control of debt levels. Keyword: Payment recording, Manual system, School Payment Receivables, Comparison, Advantages and Disadvantages